Photocatalytic degradation of nonylphenol by immobilized TiO2 in dual layer hollow fibre membranes - Dzinun, Hazlini (Elsevier, 2015)
A photocatalytic reactor based on novel dual-layer hollow fibre membranes with immobilized titanium dioxide (TiO2) nanoparticles was proposed in this study and tested for the degradation of highly recalcitrant endocrine disrupting compound of nonylphenol (NP). The presence of TiO2 on the outer surface of dual-layer hollow fibres was confirmed by scanning electron microscopy (SEM), energy dispersion of X-ray (EDAX), and atomic force microscopy (AFM). The effect of TiO2 loading, where the mass fraction TiO2/PVDF was varied from 0 to 1, on the degradation of toxic NP was evaluated by high-performance liquid chromatography (HPLC). The addition of TiO2 nanoparticles showed a significant effect on the membrane pore size and NP degradation rate. The presence of TiO2 on the outer layer of dual-layer hollow fibre membranes actively functioned as a photocatalyst, with the hollow fibre of TiO2/PVDF ratio of 1 possessed the highest NP degradation rate.